Continuous dynamical decoupling of optical 171Yb+ qudits with radiofrequency fields - Zalivako, Ilia V.; Borisenko, Alexander S.; Semerikov, Ilya A.; Korolkov, Andrey E.; Sidorov, Pavel L.; Galstyan, Kristina P.; Semenin, Nikita V.; Smirnov, Vasiliy N.; Aksenov, Mikhail D.; Fedorov, Aleksey K.; Khabarova, Ksenia Yu; Kolachevsky, Nikolay N. (Frontiers in Quantum Science and Technology, 2023)
The use of multilevel quantum information carriers, also known as qudits, has attracted significant interest as a way of further scaling quantum computing devices. However, such multilevel systems usually express shorter coherence time than their two-level counterparts, which limits their computational potential. We thus propose and experimentally demonstrate two approaches for realizing the continuous dynamical decoupling of magnetic-sensitive states with mF = ±1 for qudits encoded in optical transition of trapped 171Yb+ ions. We improve the coherence time of qudit levels by an order of magnitude (more than 9 ms) without any magnetic shielding, revealing the potential advantage of the symmetry of the 171Yb+ ion energy structure for counteracting magnetic field noise. Our results are a step toward realizing qudit-based algorithms using trapped ions.